Aspectos anatômicos, qualidade fisiológica e resposta antioxidante em sementes de Peltophorum dubium (Sprengel) Taubert armazenadas, e submetidas a métodos para superação da dormência - Müller, Evelin Maria (2017)
The growing demand for seeds and seedlings of native species, due to the restoration of degraded areas, leads to the need for studies on the storage of seeds for future use. The objective of this study was to evaluate the anatomical aspects, physiological quality and antioxidant enzymatic activity of Peltophorum dubium seeds during storage, and later submitted to methods of physical dormancy (T1 - without scarification, T2 - mechanical scarification and T3 - chemical scarification with sulfuric acid for 10 minutes). The seeds were stored at 5 ° C for 12 months. At pre-established intervals, these were evaluated by water content, anatomical analysis of the tegument, electrical conductivity, percentage of germination, initial development of seedlings, antioxidant enzymatic activity and lipid peroxidation. The integument underwent anatomical changes throughout the storage. The electrical conductivity did not correspond to the physiological quality of the seeds. The percentage of germination for treatments during storage did not differ significantly, presenting a mean of 6.8% for T1, 95% for T2 and 94% for T3. The rate of germination increased after 180 days of storage when associated with treatments T2 and T3. Initial seedling development was stimulated in all treatments. There was an increase in the activity of the catalase enzyme at 60 days, the enzyme superoxide dismutase at 360 days and malondialdehyde at 60 days for all treatments, followed by a significant decrease at 300 and 360 days of storage. The storage of the Peltophorum dubium seed promoted anatomical modifications of the skin, maintained the physiological quality of the seeds, and after 180 days of storage, in association with the treatments, increased the rate ofgermination and stimulated the initial development of the seedlings. The antioxidant enzyme system proved to be efficient, due to the activity of the catalase enzyme, in order to review the oxidative damages, promoting the control of the deterioration process.